2005
DOI: 10.1007/s00424-005-1484-5
|View full text |Cite
|
Sign up to set email alerts
|

Water permeability in human airway epithelium

Abstract: Osmotic water permeability (P(f)) was studied in spheroid-shaped human airway epithelia explants derived from nasal polyps by the use of a new improved tissue collection and isolation procedure. The fluid-filled spheroids were lined with a single cell layer with the ciliated apical cell membrane facing the outside. They were capable of surviving hours of experiment involving continuous superfusion of the bathing medium and changes of osmolarity. A new image analysis technique was developed for measuring the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 42 publications
4
18
0
1
Order By: Relevance
“…The apical membranes face the outside, and basolateral membranes line the lumen of the spherical organoids ( Figure 1). This orientation has been observed by other groups when nondisrupted epithelial sheets are cultured in suspension (40)(41)(42)(43)(44). When CFTR is labeled with a highly specific monoclonal antibody raised against the NBD2 region of CFTR (Ab 528, provided by J.R. Riordan, UNC-Chapel Hill; refs.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The apical membranes face the outside, and basolateral membranes line the lumen of the spherical organoids ( Figure 1). This orientation has been observed by other groups when nondisrupted epithelial sheets are cultured in suspension (40)(41)(42)(43)(44). When CFTR is labeled with a highly specific monoclonal antibody raised against the NBD2 region of CFTR (Ab 528, provided by J.R. Riordan, UNC-Chapel Hill; refs.…”
Section: Resultssupporting
confidence: 62%
“…Such samples provide a renewable source of differentiated airway epithelial cells from any individual with CF, regardless of their mutation, that does not require tissue expansion and multiple cell divisions prior to performing the assay. To improve the suitability of these samples for both functional and morphological tests, we have developed an organoid culture that is similar to cultures reported previously, where the apical ciliated membrane orients to the media bath (40)(41)(42)(43) but is derived from simple nasal epithelial curettage. This minimally invasive technique does not require polyp excision, which is different from the earlier reports, and utilizes normal nasal epithelial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…CF cultures had similar water permeability to non-CF cultures, consistent with our RT-PCR data (Fig. 3C) and with previous reports (8,9).…”
Section: Discussionsupporting
confidence: 92%
“…Recent data from spheroid explants of human nasal polyps provided evidence for AQP5 function in airway epithelia. In these large, spherical airway cell monolayers, with the ciliated apical membrane facing outward, Pederson et al (9) reported high membrane P f (ϳ150 m/s) that was sensitive to brief exposure to low concentration mercury. Here, our high P f values for HBE cultures and the weak temperature dependence of permeability suggest AQPmediated water movement (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation